Insights from a mixed-methods Delphi study into the global airline industry - Ellis, Darren (Inderscience, 2022)
This paper looks at the key methodological and design insights gained from a five-stage mixed methods Delphi study investigating the global airline industry's likely future strategic trajectory. The exploratory study sequentially unfolded across a workshop, test/pilot survey, main survey 1, main survey 2, and finally in-depth interviews. The study revealed the important roles each stage played in gathering a wide array of salient data and informing subsequent stages and analysis. This research journey demonstrated the versatility available when mixing quantitative and qualitative methods in a Delphi study covering air transport, and how each can reinforce and complement the other. This is particularly relevant when investigating emerging air markets, where existing data are either limited or non-existent. Although a geographically dispersed multidisciplinary cohort of participants contributed to this study, more expert voices from under-researched emerging regions and air markets are evidently required for future research into this still expanding global industry.
Keywords: Delphi study; emerging air markets; mixed methods; global airline industry; strategic forecasting; liberalisation; protectionism; industry level analysis